REDD‐1 aggravates endotoxin‐induced inflammation VIA atypical NF‐κB activation. Issue 8 (16th March 2018) - Lee, Dong‐Keon; Kim, Ji‐Hee; Kim, Joohwan; Choi, Seunghwan; Park, MinSik; Park, Wonjin; Kim, Suji; Lee, Kyu‐Sun; Kim, Taesam; Jung, Jiwon; Choi, Yoon Kyung; Ha, Kwon‐Soo; et al.
Abstract : Regulated in development and DNA damage responses 1 (REDD‐1), an inhibitor of mammalian target of rapamycin (mTOR), is induced by various cell stressors, including LPS, a major player in the pathogenesis of endotoxemic shock. However, the pathologic role of REDD‐1 in endotoxemia is largely unknown. We found that LPS increased REDD‐1 expression, nuclear transcription factor‐kB(NF‐kB) activation, and inflammation and that these responses were suppressed by REDD‐1 knockdown and in REDD‐1 +/− macrophages. REDD‐1 overexpression stimulated NF‐κB‐dependent inflammation without additional LPS stimulation. REDD‐1‐induced NF‐κBactivation was independent of 2 classic IKK‐dependent NF‐κB pathways and the mTOR signaling pathway; however, REDD‐1, particularly its C‐terminal region (178‐229), interacted with and sequestered IκBα, to elicit atypical NF‐κB activation during the delayed and persistent phases of inflammation after stimulation. Moreover, REDD‐1 knockdown mitigated vascular inflammation and permeability in endotoxemic mice, resulting in decreases in immune cell infiltration, systemic inflammation, caspase‐3 activation, apoptosis, and consequent mortality. We further confirmed the inflammatory and cytotoxic effects of REDD‐1 in endotoxemic REDD‐1 +/− mice. Our data support the likelihood that REDD‐1 exacerbates endotoxemic inflammation via atypical NF‐κB activation by sequestering IκBα.—Lee, D.‐K., Kim, J.‐H., Kim, J., Choi, S., Park, M., Park, W., Kim, S., Lee, K.‐S., Kim, T., Jung, J., Choi, Y.K., Ha, K.‐S., Won, M.‐H., Billiar, T.R., Kwon, Y.‐G., Kim, Y.‐M. REDD‐1 aggravatesendotoxin‐induced inflammation via atypical NF‐κB activation. FASEB J . 32, 4585‐4599 (2018). www.fasebj.org